Medical honey in professional wound care. (February 2013) - Biglari, Bahram; Swing, Tyler; Büchler, Axel; Ferbert, Thomas; Simon, Arne; Schmidmaier, Gerhard; Moghaddam, Arash
Many physicians and wound care professionals still think honey is a 'folk remedy' with no scientific evidence for its use in modern wound care. They believe that after the development of antibiotics and professional treatment strategies, the use of honey to treat wounds is obsolete. Researchers have shown that honey derived from Leptospermum scoparium, so called manuka honey, displays significant antibacterial effects on all clinically relevant bacterial species and also works well in combination with antibiotics. Of particular interest has been manuka honey's intriguing activity against methicillin-resistant Staphylococcus aureus . Hospitals all over Germany, New Zealand, Australia and Austria are convinced of its benefits and use it regularly. Medical-grade honey and ready-to-use honey dressings are widely available in the EU since 2004. This manuscript intends to deal with the benefits of medical honey in professional wound care.